2018
DOI: 10.1021/acsomega.8b00785
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Dye Aggregation in Sodium Dodecylsulfate-Stabilized Poly(methylmethacrylate) Nanoparticles as Fluorescent Imaging Probes

Abstract: Polymer nanoparticles are used extensively in biomedical applications. Poly(methylmethacrylate) (PMMA) nanoparticles obtained via nanoprecipitation were unstable and flocculate or precipitate from solution within a few hours. A simple method to improve the stability of the particles using surfactants at low concentrations was carried out to produce PMMA nanoparticles with long-term stability in water (>6 months). The increased stability was attributed to the incorporation of surfactants inside the polymer part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 55 publications
8
28
0
Order By: Relevance
“…The absorption maxima of the NPs were at 445 nm and 470 nm, and emission maximum was at 550 nm, respectively, which is identical to the solution spectrum of the dye 29 . From the absorbance and emission spectra, spectral inversion or bathochromic shift characteristic of dye aggregation in the NPs was not observed 28 , indicating homogenous distribution of dye inside the polymer NPs. The order of mixing of organic polymer solution with water has an impact on the NP size distribution.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The absorption maxima of the NPs were at 445 nm and 470 nm, and emission maximum was at 550 nm, respectively, which is identical to the solution spectrum of the dye 29 . From the absorbance and emission spectra, spectral inversion or bathochromic shift characteristic of dye aggregation in the NPs was not observed 28 , indicating homogenous distribution of dye inside the polymer NPs. The order of mixing of organic polymer solution with water has an impact on the NP size distribution.…”
Section: Resultsmentioning
confidence: 93%
“…For the current investigation, we are interested in exploring the uptake and translocation of NPs of two most common polymers, PVC and PMMA and investigated the induced cellular biochemical changes using baby hamster kidney cells (BHK—21) as a model. For easy tracking purpose, fluorescent perylene dye incorporated NPs were prepared from these two polymers using the nanoprecipitation method 28 and fully characterized. Both mechanisms of intake of the luminescent polymer NPs and biochemical changes occurring inside the cells are discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoprecipitation is a kinetically controlled process where parameters such as concentration, temperature, addition rate and presence of stabilizer influence the formation of stable particle . Sodium dodecyl sulfate (SDS, 10 mg), and the appropriate pyrene compound (10 mg) were dissolved in tetrahydrofuran (50 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Solar cell acceptors based on perylene bisimide coupled with pyrene demonstrated promising power conversion efficiency, which was due to the broad absorption and π‐electron delocalization leading to effective charge transport , . Also, the previous findings from our group demonstrated that perylene tetraester (PTE) based dyes are non‐toxic towards mammalian cells and could be used in bioimaging applications due to their intense fluorescence emission and high photochemical stability …”
Section: Introductionmentioning
confidence: 95%
“…The simplest approach uses optical spectroscopy, where the dye aggregation or leakage can lead to changes in the absorption and emission wavelengths. [151][152][153][154] One of the most powerful methods to study particle integrity is Forster resonance energy transfer (FRET). Since short donor-acceptor distances are required for the efficient FRET (2-10 nm), one should achieve mm concentrations of dyes to realize FRET inside the nanodroplets.…”
Section: Stability Of Dye-loaded Nes and Cargo Releasementioning
confidence: 99%